Perancangan Sistem Informasi Penjadwalan Produksi Berbasis Engineering to Order di Bengkel Custom Wolfson Motorworks - Yusuf Mauluddin; Ridwan Setiawan; Wibawa Dewantara (Jurnal Algoritma, 2022)
In the production process of custom motorbikes based on Engineering to Order, it is possible to estimate the time for the production process, but it is not certain when the motorbike will be finished on time, so delays often occur where the estimated time given to consumers does not match the work process time in the field. The purpose of this research is to design a production scheduling information system in the form of a prototype so that builders are able to provide information about the development of the production process in the "Wolfson Motorworks" custom workshop. The method used is the prototype model and the Unified Modeling Language (UML) and the diagrams used are use case diagrams. This research only reaches the system model prototype that can be simulated using the figma application. The result of this research is the success of production scheduling in the form of SOPs for making structured custom motorbikes, a combination of work has been carried out by utilizing existing human resources and the concept of making custom motorbikes as many as 3 motorbikes if done simultaneously and system design in the form of a prototype with a sample navigation system.